Conversational Analysis of Interruption in Suits Series Season 1 - Winda Afrina; Yusuf, Muhammad; Hanafiah, Ridwan (Talenta Publisher, 2022)
This research aims to find out the types of interruptions based on Ferguson’s theory in Beattie (1982) and the functions of interruptions based on Kennedy and Camden’s theory in Li (2001) in Suits Series Season 1. It was conducted by using descriptive qualitative method, while the data were all utterances taken from the Suits Series Season 1. The results showed that from four types of interruption, there was only one type unfound with 70 occurrences in total of interruptions found in Suits Series Season 1. Simple interruptions were used most in the series with 50 occurrences, followed by 18 occurrences of overlap interruptions, and 2 occurrences of butting-in interruptions, and no silent interruption found. The results also showed that there were six of seven functions of interruptions found in the research. The most found function was floor taking with 22 occurrences, followed by 13 occurrences of agreement, 12 occurrences of topic change, 10 occurrences of clarification, 9 occurrence of assistance, 4 occurrences of disagreement, and no tangentialization found. This means that the use of interruptions in characters’ utterances of Suits Series Season 1 mostly was to take the floor from the other speaker and propose another topic to discuss.